2008
DOI: 10.4028/www.scientific.net/jnanor.2.129
|View full text |Cite
|
Sign up to set email alerts
|

Blood Platelet’s Behavior on Nanostructured Superhydrophobic Surface

Abstract: Abstract. Regular arrays of micro-pillars and nano-grooves structures on the silicon wafer are fabricated by using soft lithography, and the three dimension morphology of textured surface is observed by using scanning electron microscopy (SEM) and atomic force microscope (AFM). The static water contact angles are measured by using contact angle meter to characterize the wettabilities of these surfaces. To investigate how the presence of topography and the variations of wettability affect the haemocompatibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 16 publications
1
37
0
Order By: Relevance
“…A few studies reported the influence of surface nanostructure on platelet adhesion (see Section 1 and Refs. [35][36][37][38][39][40][41]). The surface topography produced here by colloidal lithography could increase the contact area with the platelets if the latter were able to deform in order to follow the surface relief.…”
Section: Effect Of Surface Chemistry and Topographymentioning
confidence: 97%
See 2 more Smart Citations
“…A few studies reported the influence of surface nanostructure on platelet adhesion (see Section 1 and Refs. [35][36][37][38][39][40][41]). The surface topography produced here by colloidal lithography could increase the contact area with the platelets if the latter were able to deform in order to follow the surface relief.…”
Section: Effect Of Surface Chemistry and Topographymentioning
confidence: 97%
“…A few attempts to influence platelet adhesion through substrate nanostructuration have been reported [35][36][37][38][39][40][41]. Platelet adhesion was decreased or increased by the presence of nanogrooves at the surface of poly(dimethyl siloxane) [38] or poly(caprolactone) [37], respectively. Vertically aligned carbon nanotubes, associated with a polymer matrix, were used to reduce platelet adhesion [36,41].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Zhou et al found a novel strategy for the significant improvement of the blood compatibility of nanostructured trichloro (1H,1H,2H,2H-perfluorooctyl)silane on silicone ( Figure 6). 76 Mao et al…”
Section: Applications Of Lotus-leaf-like Structures In Medical Fieldsmentioning
confidence: 99%
“…TNTs are usually superhydrophilic [24,35], and can greatly improve hemocompatibility or corrosion resistance as discussed above. On the other hand, superhydrophobic materials have also been reported to improve either hemocompatibility [24,[37][38][39][40] or corrosion resistance [41,42]. Thus, both superhydrophobic and superhydrophilic TNTs could be promising coatings for blood contact materials such as SS.…”
Section: Introductionmentioning
confidence: 97%